(untitled) (Philologia, 2021)
The differences between the Canadian and American variations of English are not clearly perceptible to the un/trained ear, as the two exhibit a considerable degree of homogeneity. We can account for this phenomenon by discussing several criteria such as historical development, geographical distribution, morphosyntax, phonology and lexicon. This paper will serve as a guide to the current similarities as well as dissimilarities Canadian English has with American English and to a lesser extent British English.